PENGARUH KEMAMPUAN KERJA, KEMATANGAN PEGAWAI, LOYALITAS DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI DI KANTOR PELAYANAN PAJAK PRATAMA MEDAN BARAT - Jonathan Sitompul; Sahata Sinambela; Yanto Silaban; Amandan Pane; Frans Jhon Sukses Tarigan (JRMB (Jurnal Riset Manajemen & Bisnis), 2021)
This research was conducted to analyze the problem how is the influence of work ability, employee maturity, loyalty and work discipline partially and concurrently on the performance of employees work in the Kantor Pelayanan Pajak Pratama Medan Barat? Research objectives: To determine the effect of work ability, employee maturity, loyalty and work discipline partially and simultaneously on the performance of employees work in the Kantor Pelayanan Pajak Pratama Medan Barat. The hypothesis proposed is: There is a significant effect of work ability, employee maturity, loyalty and work discipline partially and jointly on the performance of employees work in the Kantor Pelayanan Pajak Pratama Medan Barat. The study was conducted at the Kantor Pelayanan Pajak Pratama Medan Barat Jalan Jalan Asrama No. 7-A, Medan, with a population of 88 people, and a study sample of 86 people. Based on the analysis results obtained work ability have a positive and significant effect on the performance of employees work of the Kantor Pelayanan Pajak Pratama Medan Barat, this is supported by the results of t count analysis t-table (4,813 1,989) at n = 86 at 95% significance level. Employee maturity has a not effect on the performance of employees work of the Primary Tax Service Office of Medan Barat, this is supported by an analysis of t count t-table (1,646 1,989) at n = 86 at 95% significance level. Loyalty has a not effect on the performance of employees work of the Kantor Pelayanan Pajak Pratama Medan Barat, this is supported by an analysis of t count -table (0,382 1,989) at n = 86 with a significant level of 95%. Work discipline has a effect on the performance of employees work of the Kantor Pelayanan Pajak Pratama Medan Barat, this is supported by an analysis of t count -table (4,112 1,989) at n = 86 with a significant level of 95%. Value of F-count F table (24,154 2,48) This states that together (multiple) there are positive and significant effects of work ability, employee maturity and loyalty on the performance of employees work of employees of the Kantor Pelayanan Pajak Pratama Medan Barat. Thus the hypothesis proposed is accepted by the truth.